Hybrid beamforming design for orthogonal frequency division multiplexing dual‐function radar‐communication system with optimised transmit beampattern. Issue 7 (26th May 2022) - Xiao, Weihuang; Chu, Ping; Liao, Bin
Abstract: In this paper, the problem of hybrid beamforming design in an orthogonal frequency division multiplexing dual‐function radar‐communication system to achieve optimised transmit beampattern subject to the constraints of communication performance and transmit power is investigated. Specifically, the analogue beamformer and digital beamformer for each subcarrier at the transmitter are designed by maximising the integrated mainlobe‐to‐sidelobe ratio (IMSR) of the transmit beampattern under the restriction of the communication signal‐to‐interference‐plus‐noise ratio (SINR). Since the design problem is a complicated fractional programing problem, the quadratic transform technique is introduced for problem simplification. Under the framework of a consensus‐alternating direction multiplier method, the solutions to the subproblems in the iterations are presented in detail. Finally, simulation results are demonstrated to verify the effectiveness of the proposed algorithm.